Step-by-Step: Insights on key marine organisms associated with coral reef benthic cover using Stepwise Multivariate Regression - Wee Hin Boo; Affendi Yang Amri; Then Amy Yee Hui; Chen Sue Yee; Hyde Julian (E3S Web of Conferences)
Coral reef ecosystems are severely threatened by human activities and climate change. However, the complexity of the ecosystem can complicate identification of significant ecological interactions between the organisms and the reef system. Thus, this study used a ten-year citizen science reef monitoring dataset by Reef Check Malaysia to identify key reefassociated organisms (fish and invertebrates) affected by the changes in benthic cover using Stepwise Multivariate Regression. Data collection started in 2013 to 2023, covering 148 sites from 23 islands of East Coast Peninsular Malaysia. The most dominant biotic benthic cover in coral reefs is the Hard Coral (mean 48.7±19.4% median = 49.4%), followed by Rubble (8.28±11.0%,3.75%), and Nutrient Indicator Algae (4.96±9.15%, 1.25%). Stepwise Multivariate Regressions showed that 6 out of 9 keystone fishes and 4 out of 8 keystone invertebrates were significantly correlated with each individual benthic cover. The regression models indicated that Butterflyfish, Grouper, Sweetlips, Snappers, Diadema Urchins are susceptible to the deterioration of coral reefs (reduction of Hard Coral and increase of Rubble and Nutrient Indicating Algae), while Sea Cucumber, Giant Clam and Pencil Urchin may flourish. Henceforth, the shortlisted reef-associated organisms can be an accessible and cost-effective targeted organisms for a quick and simple assessment of coral reef health.